2024
DOI: 10.1002/wea.4531
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of the severity of the 2022 drought and its impacts

Lucy J. Barker,
Jamie Hannaford,
Eugene Magee
et al.

Abstract: The summer of 2022 was particularly notable for the prolonged and extensive hot and dry conditions experienced across the UK. The resultant 2022 drought had widespread impacts and prompted much discussion about the continuing vulnerability of the UK to drought, particularly in the context of anthropogenic warming. Here, we briefly describe the evolution of the drought before focusing on the severity of rainfall, river flow, soil moisture and groundwater level deficits from summer 2022, placing the event into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…CC BY 4.0 License. markedly in 2022 (Barker et al, 2024). The plot also suggested that most media coverage for major droughts coincided when the meteorological condition consisted of both positive temperature and negative precipitation anomalies (see the yellow shades).…”
Section: Interplay Between Meteorological Conditions On Media Coveragementioning
confidence: 90%
See 1 more Smart Citation
“…CC BY 4.0 License. markedly in 2022 (Barker et al, 2024). The plot also suggested that most media coverage for major droughts coincided when the meteorological condition consisted of both positive temperature and negative precipitation anomalies (see the yellow shades).…”
Section: Interplay Between Meteorological Conditions On Media Coveragementioning
confidence: 90%
“…Extracting entity names, such as frequently mentioned organization names within the sub-corpora, was also performed. and the drought in mid-2022 (Drought in Summer 2022 hereafter), which were reported as extreme droughts on the one hand by the official reports of the Centre for Ecology & Hydrology (i.e., Major Hydrological Events) and research papers (e.g., Barker et al, 2024), and on the other by looking at the times in which massive media coverage was accumulated in the heatmap above. At this point, we looked into the headlines and body content corresponding to the topics to further understand the context in which these droughts were represented.…”
Section: Media Topic: Topic Modellingmentioning
confidence: 99%
“…July 2022 was exceptionally warm and dry in the UK, with widespread record-breaking maximum temperatures and extremely low rainfall across England (<10% of average over large parts of the south-east) (Barker et al 2024). The preceding months had also been dry, leading to river flows and reservoirs reaching exceptionally low levels across much of England and the introduction of temporary use bans by several water companies in southern England (Barker et al 2024).…”
Section: Summer 2022 Droughtmentioning
confidence: 99%
“…July 2022 was exceptionally warm and dry in the UK, with widespread record-breaking maximum temperatures and extremely low rainfall across England (<10% of average over large parts of the south-east) (Barker et al 2024). The preceding months had also been dry, leading to river flows and reservoirs reaching exceptionally low levels across much of England and the introduction of temporary use bans by several water companies in southern England (Barker et al 2024).…”
Section: Summer 2022 Droughtmentioning
confidence: 99%